Metastable ferromagnetic flux closure-type domains in strain relaxed Gd0.1Ca0.9MnO3 thin films - Schulman Alejandro; Palonen Heikki; Lähteenlahti Ville; Beiranvand Azar; Huhtinen Hannu; Paturi Petriina (IOP PUBLISHING LTD, 2022)
We have systematically studied the structural, electrical transport, and magnetic properties of Gd0.1Ca0.9MnO3 thin films in function of thickness, which ranged from 22 nm up to 220 nm. We have found that, although no strong substrate-induced strain was detected for any thickness, a sudden change in the electric transport properties was observed when the film thickness increases above 80 nm. While thinner samples are insulating in the whole temperature range, the samples thicker than 80 nm show a clear insulator-to-metal transition (IMT) at around 100 K. The IMT coincides with the appearance of a ferromagnetic phase that is absent in the thinner samples. We associate this change in behavior with a critical film thickness that induces a sudden change in domain configuration, from in-plane domain to a closed flux-type domain with out-of-plane orientations. These out-of-plane oriented domains are meta-stable ferromagnetic in nature and result in an IMT which is accompanied by a hysteretic magnetoresistance behavior.